EFFECT OF ANEMIA IN YPOTHYROIDISM - A.J.MANJULADEVI,; D.HEMALATHA,; B.SHANTHI, (International Journal of Pharma and Bio Sciences, 2015)
Hypothyroidism is a clinical syndrome resulting from deficiency of thyroid hormones in the target tissues, leading to a generalized slowing of all metabolic processes. Erythrocyte abnormalities are frequently associated with thyroid disorder. The aim of our study is to know the role of anemia and its significance in untreated and treated primary hypothyroidism patients.This study included 150 subjects which are untreated primary hypothyroid (n=50), treated primary hypothyroid (n=50) and euthyroid (n=50). This study was carried out at Department of Biochemistry, Sree Balaji Medical College and hospital. The thyroid profile of the subjects was assessed along with hematological parameters (Hb, HCT, RBC, and MCV). MCV is a significant parameter to study the types of anemia. In these study hematological parameters in the following groups: untreated primary hypothyroid, treated hypothyroid and euthyroid were compared. Its found that hematological parameters like Hb, RBC, MCV, HCT were significantly decreased in untreated hypothyroidsm, with the p value being less than 0.05 whereas, in treated Hypothyroid, results were in acceptable range. . In untreated primary hypothyroid, Hb (10.70±0.86 g/dl), RBC (4.63±0.51 ×10â¶/μl), MCV (83.34±6.92 FL), and HCT (38.6±2.6%) suggesting risk for developing anemia. Anemia is found to be associated with hypothyroidism. Untreated hypothyroid cases are more prone to develop anemia. This signifies prompt identification and treatment is necessary in thyroid dysfunction so as to prevent the effects. Hence, in conditions with anemia of any cause, ruling out hypothyroid is significant.